Respostas

2014-03-15T10:31:28-03:00
A = 3x² - 7x - 5 e B = 2x² - 8x + 2
----------------------------------------------------------------------------------------------- 
A + B = (3x² - 7x - 5) + (2x² - 8x + 2)
             3x² - 7x - 5 + 2x² - 8x + 2
             3x² + 2x² - 7x - 8x + 2 - 5 
             5x² - 15x - 3
----------------------------------------------------------------------------------------------- 
A - B = (3x² - 7x - 5) - (2x² - 8x + 2)
             3x² - 7x - 5 - 2x² + 8x - 2
             3x² - 2x² - 7x + 8x - 2 - 5 
             x² + x - 7
1 5 1